Port heritage as a tourist asset and a lever for urban renewal: the case of the Bay of Pasaia (Gipuzkoa) - De Rosa-Giolito, Enrique Rafael (Revista de Estudios Andaluces, 2024)
The aim of this research is to explore the convergence of the tourism sector with the cultural industries and to orient the heritage field towards concerted planning at two levels. The first focuses on public administration and multilevel governance, fostering dialogues to overcome conflicts. The second focuses on approaching a sustainable economic transition by bringing together different actors. The methodology uses a geo-historical model that takes into account modes of production, society and space; issues that became more evident in times of pandemic. In addition, 38 semi-structured interviews were carried out with specialist territorial agents in which qualitative information on this subject was obtained, allowing the study of subjective meanings, attitudes and opinions, between people and their environment, as a result of their experience in everyday life. Together with a systematisation of documentation and information. By means of a territorial diagnosis, the current conditions of the port-city relationship and the case study of Albaola together with the museums of the region are shown. The conclusions demonstrate the need for concertation between the various actors and a common institutional and social proposal agreed by consensus, based on a strategic action plan.